Peran Advokasi Pekerja Sosial Terhadap Anak Korban Kekerasan Seksual Di UPT Kementerian Sosial Sentra Bahagia Medan - Simanullang, Jodis Openri; Asbi, Erni Asneli (Jurnal Intervensi Sosial dan Pembangunan, 2025)
Sexual violence against children is a very complex social problem, so advocacy support for children’s recovery is needed from various parties, especially Social Workers who provide intervetions to prevent and restore social dysfunction, both in individuals, groups, and society. Sexual violence against children can have an impact on the child’s physical and psycological condition, so this research aims to determine the advocacy role of Social Workers for child victims of sexual violence at Sentra Bahagia and the obstacles they face. This research was conducted at Sentra Bahagia Medan. This type of research is qualitative with a descriptive approach. Data collection techniques were obtained form primary data through observation, interviews documentation, as well as secondary data through literature studies, journals, books internet sources. The research results show that the role of Social Workers in advocacy support for child victims of sexual violence at Sentra Bahagia is to provide assistance, protection, education and facilitation, both in the child’s recovery process and in the process of resolving children’s cases. The obstacles faced by Social Workers include: lack of family participation due to a number of factors such as residence outside the city of Medan and the family's economic conditions which are still difficult; the child's psychosocial condition which influences the difficulty of cooperation in determining joint decisions due to the trauma they have experienced; and changes in the service paradigm at Sentra Bahagia.Keywords: Advocacy, Social Worker, Children, Sexual Violence.